Analysis of Changes in the Coastaline of Tabailenge Island North Morotai District, Morotai Island Regency - Kismanto Koroy; Nurafni; Marlin Chrisye Wattimena; Iswandi Wahab (East Asian Journal of Multidisciplinary Research, 2023)
Shoreline change is a process that occurs dynamically and changes in sea bathymetry. The process of adjusting the coastline is continuously carried out for a natural balance against various impacts that can affect changes in the coastline. The process of changing the coastline can occur naturally and is anthropogenic. Based on this description, it is necessary to study/research changes in the coastline seen from oceanographic factors in the form of currents on Tabailenge Island, North Morotai District, Morotai Island Regency. This research was conducted in November 2022 in the waters of Tabailenge Island, South Morotai District, Morotai Island Regency. Analysis was conducted using field data (primary) and Google Earth software image data (secondary). Analysis was carried out using image data from different years (2009, 2011, 2016, 2019, and 2021). The research phase begins with preparing photo image data that will be analyzed for changes in the coastline using satellite imagery from the Google Earth application for the observation periods of 2009, 2011, 2016, 2019, and 2021. Image data use the JPEG format for different months of observation depending on availability. Cloud-free data contained in Google Earth. Based on data from image interpretation in 2009, 2011, 2016, 2019, and 2021, digitization has been carried out to show that there has been a change in the coastline from year to year. Observation of image data for a period of ± 10 years shows that changes in the coastline occur due to the influence of oceanographic parameters such as currents.